2023
DOI: 10.1021/acsomega.3c00191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chitosan-Silver Nanocomposite and Its Evaluation as an Antibacterial Coating for Mobile Phone Glass Protectors

Gibson Jake C. Canama,
Monica Claire L. Delco,
Rhoel A. Talandron
et al.

Abstract: An easy and environment-friendly route for antibacterial coating suited for mobile phone glass protectors was successfully demonstrated. In this route, freshly prepared chitosan solution in 1% v/v acetic acid was added with 0.1 M silver nitrate solution and 0.1 M sodium hydroxide solution and incubated with agitation at 70 °C to form chitosan-silver nanoparticles (ChAgNPs). Varied concentrations of chitosan solution (i.e., 0.1, 0.2, 0.4, 0.6, and 0.8% w/v) were used to investigate its particle size, size distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
(185 reference statements)
1
11
0
Order By: Relevance
“…Both AgNPs-CH nanocomposites show a shift of the chitosan peak from 1544 cm −1 to 1636 cm −1 due to interactions formed between chitosan and AgNPs. These shifted peaks are associated with bending N-H vibrations from -NH 2 amine groups [ 68 , 71 , 72 , 73 ], a result which suggests the interaction between chitosan and AgNPs. This stretching may appear due to the electrostatic interaction of Ag with the -NH 2 group of chitosan [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both AgNPs-CH nanocomposites show a shift of the chitosan peak from 1544 cm −1 to 1636 cm −1 due to interactions formed between chitosan and AgNPs. These shifted peaks are associated with bending N-H vibrations from -NH 2 amine groups [ 68 , 71 , 72 , 73 ], a result which suggests the interaction between chitosan and AgNPs. This stretching may appear due to the electrostatic interaction of Ag with the -NH 2 group of chitosan [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this hydrophobic attribute offers anti-fingerprinting functionality when applied to touchscreens. Moreover, high transmittance, antireflective capabilities, and robust mechanical durability are prerequisites for touchscreen displays [ 69 , 70 ]. Thus, there is significant interest in developing antimicrobial coating materials that encompass additional traits like transmittance, hydrophobicity, and mechanical properties.…”
Section: Antibacterial Polymer Composites For Display Coating Applica...mentioning
confidence: 99%
“…In the study by Canama et al [ 70 ], some sugars were used in a composite with antibacterial materials to improve their performance. The authors successfully demonstrated an environmentally friendly method for antibacterial coating on mobile phone glass protectors using chitosan–silver nanoparticles (ChAgNPs).…”
Section: Antibacterial Polymer Composites For Display Coating Applica...mentioning
confidence: 99%
“…Carbohydrate polymers such as hyaluronic acid, chitosan, alginate, and cellulose are widely used as capping agents during the synthesis of AgNPs because these polymers are generally considered to be chemically stable, nontoxic, biocompatible, and biodegradable. 15,[26][27][28][29][30][31][32][33][34][35][36][37][38] Among them, hyaluronic acid-capped AgNPs (HA-AgNPs) have attracted a great deal of attention due to their unique properties and have been studied in different research areas such as antibacterial coating, in vivo imaging, wastewater treatment, drug delivery, sensing, and cancer therapy. [39][40][41][42][43][44][45][46][47][48] Even though several research papers have been published on HA-AgNP-based bioactive materials, there are currently no reports on the catalytic investigation of HA-AgNPs as biocompatible and nontoxic catalysts in catalytic oxidation processes.…”
Section: Introductionmentioning
confidence: 99%